Nasal CPAP in the Pediatric Ward to Reduce PICU Admissions for Severe Bronchiolitis? - Melodie O. Aricò; Diana Wrona; Giovanni Lavezzo; Enrico Valletta (MDPI AG, 2023)
In treating acute bronchiolitis in infants, the decision to use continuous positive airway pressure (CPAP) often involves infant referral from the pediatric ward to the pediatric intensive care unit (PICU). We present our experience of CPAP use in a general pediatric ward, aiming to reduce the pressure on the PICU in recent outbreaks of bronchiolitis. Clinical data of patients less than 12 months of age and admitted for bronchiolitis from 1 October 2021 to 31 March 2023 were retrospectively collected. Of 82 infants admitted for bronchiolitis, 16 (19%) were treated with nasal CPAP (nCPAP group); of the remaining 66, 21 (26%) were treated with a low-flow nasal cannula (LFNC) only, 1 (1%) was also treated a with high-flow nasal cannula (HFNC), 12 (15%) were treated with an HFNC only, and 41 (50%) were treated without oxygen support (no-nCPAP group). Overall, coinfection with RSV and SARS-CoV-2 was observed in three patients and SARS-CoV-2 infection was observed in two patients. None of them required any type of oxygen support. Only 3/16 (19%) infants in the nCPAP group were referred to the PICU due to worsening clinical conditions despite nCPAP support. In our experience of treating epidemic bronchiolitis, nCPAP can be safely managed in a general pediatric ward, thus reducing the burden of admissions to the PICU. Training and regular updating of the pediatric staff, careful monitoring of the patient, and close cooperation with the PICU were instrumental for our team.